Hedonistic Shopping Motivation and Price Discounts for Impulsive Purchases of Shopee e-Commerce Users Baiturrahmah University Students - Amijah, Amijah; Yoda, Tilawatil Ciseta; Malik, David (ADPEBI, 2024)
The growth of e-commerce in Indonesia has developed, judging from marketing activities, purchases consist of two types, namely planned purchases and unplanned purchases. Impulse purchases are a consumer attitude that can certainly increase the company's profits. The purpose of this study is to find out how the influence of hedonistic shopping motivation and price discounts on impulse purchases of e-commerce users of Baiturrahmah University students. The type of research used in this study is ssociative research with a quantitative approach. The population in this study is students who use Shopee e-commerce at Baiturrahmah University. The sample in this study amounted to 97 respondents. The research data collection technique was through a questionnaire using a Likert scale. The data analysis technique in this study is multiple linear regression. Based on partial statistical analysis, the hedonistic shopping motivation variable was obtained t calculated 7.299 > t table 1.661 with a sig value (0.000 < 0.050) meaning that H1 was accepted and H0 was rejected, so it can be concluded that hedonistic shopping motivation has a positive and significant effect on the impulse purchase of Shopee e-commerce users Baiturrahmah University students. The price discount variable was obtained t calculated 1.473 < t table 1.661 with a sig value (0.144 > 0.050) meaning that H2 was rejected and H0 was accepted, so it can be concluded that price discount has no effect on the impulse purchase of hopee e-commerce users of Baiturrahmah University. The results of the F test were known that the f value was calculated as 53.894 > f table 3.09 with a sig value (0.000 < 0.050), meaning that H3 was accepted and H0 was rejected. It can be concluded that hedonistic shopping motivation and price discounts simultaneously have a positive and significant effect on the impulse purchase of Shopee e-commerce users of Baiturrahmah University students.